La science‑fiction institutionnelle chez Julian Bleecker et Brian David Johnson - Thomas Michaud (ReS Futurae)
Since the end of the 2000s, new practices aimed at creating science fiction within companies and organizations have been the subject of theorization. This article focuses on the two most popular methods, design fiction, by Julian Bleecker and the Near Future Laboratory, and science fiction prototyping by Brian David Johnson, of the Intel company. After presenting the guiding principles of these new practices of creativity, this study theorizes institutional science fiction, that is to say science fiction produced by institutions with the aim of innovation. Therefore, this approach, which could well constitute a new trend, partly distorts this imaginary of its traditional characteristics, and in particular of its critical negativity, theorized by Fredric Jameson.Two main possibilities are considered regarding the narratives produced by institutions. Firstly, this science fiction retains its critical negativity and directs it towards actors hostile to the interests of the institution. These could be competitors of a company, enemies of an army, social groups condemned by an interest group such as an association or a state, etc. Secondly, this science fiction develops an apologetic positivity. It is described as ideotopic, that is to say an imaginary praising the interests of an institution, therefore ideological, through a utopian and performative story.